Rota de ação da prostaglandina F22α administrada via submucosa vulvar na luteólise de bovinos - Rovani, Monique Tomazele (2011)
The aim of this study was to verify if prostaglandin F2α (PGF2α) administered by intravulvosubmucous (IVSM) injection induces luteolysis by reaching the corpus luteum (CL) directly by a local absorption rote, preventing its metabolism in the lungs, or after absorption and distribution via the systemic circulation. In a first trial, the estrus rate of 1,937 beef cows was monitored for 5 days (25.6% of estrus). At day 5, the cows that did not show estrus received 1/5 of the standard dose of dinoprost IVSM (5 mg; n = 1440) and resulted in 68.2% of estrus in the next 5 days. However, in a second trial, the number of heifers detected in estrus after dinoprost injected via the IVSM (47.4%; n = 97) or intramuscular route (IM; 54.7%; n = 95) at day 5 was not different (P > 0.05). Based on serum progesterone concentrations, animals treated with 5 mg dinoprost at day 5 of the estrous cycle do not present functional luteolysis regardless of the administration route. At day 10 of the estrous cycle, luteolysis was variable in cows treated with 5 mg of dinoprost. Nevertheless, luteolysis occurred in all animals treated with 25 mg dinoprost independent of the estrous cycle day. After treatment, the PGF2α concentration did not differ in serum from uterine and jugular veins. This was further confirmed by measuring the concentration of 13,14-dihydro-15-keto- PGF (PGFM) after 5 mg dinoprost injection via the IM or IVSM route. Dinoprost IM- and IVSM-administered resulted in a similar PGFM serum pattern over time, suggesting the same absorption rate for both routes. Although anatomical evidences suggest that PGF2α injected IVSM could be taken direct to the ovaries, avoiding the systemic circulation, the results do not support this hypothesis. In summary, the route of PGF2α administration (IVSM or IM) resulted in similar serum concentrations of PGF2α, PGFM, and luteolysis. Taking all the results together, the PGF2α injection via IVSM reached the systemic circulation before reaching the ovary, and the effectiveness of low doses of PGF2α was dependent on luteal phase and not on the route of administration.